Moshe Idel : Representing God. - Tirosh-Samuelson, Hava, 1950- (Library of contemporary Jewish philosophers., 2014)
Moshe Idel, the Max Cooper Professor Emeritus at the Hebrew University of Jerusalem, and Senior Researcher at the Shalom Hartman Institute, is a world-renowned scholar of the Jewish mystical tradition. His historical studies of rabbinic, philosophic, kabbalistic, and Hasidic texts have transformed modern understanding of Jewish intellectual history.